Effect of Public Debt on Economic Growth in Nigeria - Remigius Chinwoke Ejinkonye (PhD) (International Journal of Economics and Financial Management, 2026)
This study assessed the effect of public debt on Nigeria’s economic growth. Background: Public debt denotes the liabilities incurred by the government through the process of borrowing, which could be domestic or external borrowing. It is pertinent to note that government debt burden is basically caused by her inadequate revenue or budget deficit. It is obvious that the poor management of borrowed funds and their inadequate application in the productive sectors of the economy has contributed to the sorry state of the Nigerian economy and our poor GDP. Hence, the economy is unable to guarantee the generation of future and increased revenue from which such debt can be repaid. Aims: The specific objectives were to assess the effect of domestic debt and external debt on gross domestic product in Nigeria. Methods: The data for the period 1981 to 2023 was obtained from CBN bulletin 2023, while ex-post facto research design was adopted. The data was analyzed using descriptive statistics and multiple regression. The independent variables were: domestic debt and external debt, while the dependent variable was gross domestic product (GDP). The hypotheses were tested at 5% significance level. This study adopted the Neo-classical debt theory by Williams et al., (1900). Results: Domestic debt had positive and significant effect on GDP, while external debt had negative but significant effect on GDP. The probability (f statistic) was 0.000000 while adjusted R2 value was 0.837757. Conclusion: The public debt variables contribute to economic growth in Nigeria. Recommendations: The government should ensure that borrowed funds are applied in productive sectors of the economy. The government should have plans for repayment of borrowed funds and interest.